Metabolomic data on molecular weight fractions of the cultivated fruiting body of Ophiocordyceps sinensis and their pharmacological effects on airway tissuesMendeley Data - Han-Ni Booi; Neng-Yao Goh; Mei-Kee Lee; Chyan-Leong Ng; Szu-Ting Ng; Chon-Seng Tan; Kuan-Hon Lim; Richard Roberts; Shin-Yee Fung; Kang-Nee Ting (Data in Brief, 2025)
Ophiocordyceps sinensis is a medicinal mushroom that has been traditionally used for promoting respiratory health and addressing diverse therapeutic needs.The data in this article provides insights into the metabolic profile of the cultivated fruiting body of Ophiocordyceps sinensis (xOs™) across different molecular weight (MW) fractions. The cold-water extract obtained from xOs™ was fractionated by MW into high, medium and low MW fractions using size-exclusion chromatography. The metabolic profile of each fraction was analysed through liquid chromatography-mass spectrometry. The identification of metabolites in xOs™ was validated by analysing the mass spectra of both precursor (MS) and daughter ions (MS2) with those documented in the mass spectrometry reference libraries. Additionally, the role of each metabolite was hypothesized based on existing literature to provide scientific rationale for the traditional applications of xOs™.Further investigations into the fractions of xOs™ were conducted using the organ bath approach, in which the airway relaxant effects of each fraction on isolated airway tissues from adult male Sprague-Dawley rats were examined. This information could shed light on the bioactivity of different xOs™ fractions in relaxing airway smooth muscles. Taken together, the metabolomics and pharmacological dataset of xOs™ presented in this study may serve as a reference to facilitate comparative metabolomic analyses involving Ophiocordyceps sinensis and also to support targeted isolation of bioactive components in future works.